Geochemical analysis of lateritic duricrust formation in the Cuesta and Paulista Peripheral Depression sectors of São Paulo State, southeastern Brazil - Sulato, Everton Tiago [UNESP]; Luko-Sulato, Karen [UNESP]; Godoy, Daniel [UNESP]; Neumann, Reiner; Rosolen, Vania [UNESP] (Elsevier, 2025)
This study aims to investigate rare earth elements (REE), U, Th, Pb concentrations, and Pb isotopic ratios in lateritic weathering profiles from the Cuesta and Paulista Peripheral Depression, Brazil. Sample analysis provided geochemical and mineralogical indicators of element mobilization and distribution, enhancing the understanding of weathering processes and parental inheritance in lateritic profiles. The lateritic duricrusts are composed of goethite, hematite, kaolinite, quartz, and rare magnetite, with a significant loss of basic cation, indicating intense weathering and leaching. However, weathering fronts show limited advancement toward intense laterization, likely controlled by climate, topography, parent rock composition, and drainage. A mineralogical trend distinguishes lateritic duricrusts by elevation, with hematite predominating at mid-to-high (Cuesta) and goethite predominating at low-to-mid (Peripheral Depression) elevations. REE concentrations correlate more with mineralogy than parent rock composition, with lower REE levels in hematite-rich lateritic duricrusts at higher elevations and higher REE content in goethite-rich ones from all elevations, influenced by the alteration stage of goethite-rich lateritic duricrusts. Light REE enrichment over heavy REE is observed in lateritic duricrusts, soils, and parent rock, with soils showing greater mobility and differential accumulation. Pb redistribution occurs during weathering, with lateritic duricrusts retaining intermediate isotopic signatures and soils exhibiting the most radiogenic Pb, while 207Pb/206Pb and 208Pb/206Pb ratios suggest parental inheritance among all matrices. Higher elevation lateritic duricrusts exhibit an inverse relationship between U and Pb or Th, likely driven by mineralogical stabilization, selective adsorption, and the radioactive decay of U and Th into Pb over time.
Keywords: Ferruginous duricrust; Goethite; Hematite; Laterite; Pb isotope ratio; Rare earth elements